Normal values of aortic dimensions, distensibility, and pulse wave velocity in children and young adults: a cross-sectional study - Voges Inga (Journal of Cardiovascular Magnetic Resonance, 2012)
Abstract Background Aortic enlargement and impaired bioelasticity are of interest in several cardiac and non-cardiac diseases as they can lead to cardiovascular complications. Cardiovascular magnetic resonance (CMR) is increasingly accepted as a noninvasive tool in cardiovascular evaluation. Assessment of aortic anatomy and bioelasticity, namely aortic distensibility and pulse wave velocity (PWV), by CMR is accurate and reproducible and could help to identify anatomical and bioelastic abnormalities of the aorta. However, normal CMR values for healthy children and young adults are lacking. Methods Seventy-one heart-healthy subjects (age 16.4 ± 7.6 years, range 2.3 - 28.3 years) were examined using a 3.0 Tesla CMR scanner. Aortic cross-sectional areas and aortic distensibility were measured at four positions of the ascending and descending thoracic aorta. PWV was assessed from aortic blood flow velocity measurements in a aortic segment between the ascending aorta and the proximal descending aorta. The Lambda-Mu-Sigma (LMS) method was used to obtain percentile curves for aortic cross-sectional areas, aortic distensibility and PWV according to age. Results Aortic areas, PWV and aortic distensibility (aortic cross-sectional areas: r = 0.8 to 0.9, p < 0.001; PWV: r = 0.25 to 0.32, p = 0.047 to 0.009; aortic distensibility r = -0.43 to -0.62, p < 0.001) correlated with height, weight, body surface area, and age. There were no significant sex differences. Conclusions This study provides percentile curves for cross-sectional areas, distensibility and pulse wave velocity of the thoracic aorta in children and young adolescents between their 3rd and 29th year of life. These data may serve as a reference for the detection of pathological changes of the aorta in cardiovascular disease.